Expanding Innovation Through Challenging Organization Endowments - Steven Griggs (Journal of Innovation Management, 2021)
Revolutionary innovation in mature or large organizations has been on the decline in recent years. Incremental innovation is the norm and few large organizations create evolutionary or revolutionary innovative offerings. A reason for the lack of innovation in mature or large firms is based on management practices over the last several decades. These practices have created biases in the form of an endowment effect, which results in incremental innovation. Endowment effects impact on innovation will be explored and methods to reduce the impact of endowment effect and overcome the biases are offered.